2002
DOI: 10.1046/j.1365-313x.2002.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

KCl activates phospholipase D at two different concentration ranges: distinguishing between hyperosmotic stress and membrane depolarization

Abstract: SummaryHyperosmotic stress induces the rapid formation of phosphatidic acid (PA) in Chlamydomonas moewusii via the activation of two signalling pathways: phospholipase D (PLD) and phospholipase C (PLC), the latter in combination with diacylglycerol kinase (DGK) . A concomitant increase in cell Ca 2+ becomes manifest as de¯agellation. When KCl was used as osmoticum we found that two concentration ranges activated de¯agellation: one between 50 and 100 mM and another above 200 mM. De¯agellation in low KCl concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 56 publications
3
39
0
Order By: Relevance
“…Nod factor and elicitors stimulated the production of DGPP from PA. Similar effects were found on adding Nod factor to common vetch roots (den Hartog et al, 2001), on eliciting tomato cells (Van der Luit et al, 2000), and on osmotically stressing alfalfa, tomato, Arabidopsis, tobacco (Nicotiana tabacum), and Craterostigma plantageneum (Frank et al, 2000;Munnik et al, 2000;Meijer et al, 2001Meijer et al, , 2002Munnik and Meijer, 2001). Originally, DGPP was discovered as an in vitro product of PA kinase when ATP was added to plant microsomes (Wissing and Behrbohm, 1993) and later as an in vivo product when cells were stimulated with the G-protein activator mastoparan (Munnik et al, 1996).…”
Section: Discussionsupporting
confidence: 53%
“…Nod factor and elicitors stimulated the production of DGPP from PA. Similar effects were found on adding Nod factor to common vetch roots (den Hartog et al, 2001), on eliciting tomato cells (Van der Luit et al, 2000), and on osmotically stressing alfalfa, tomato, Arabidopsis, tobacco (Nicotiana tabacum), and Craterostigma plantageneum (Frank et al, 2000;Munnik et al, 2000;Meijer et al, 2001Meijer et al, , 2002Munnik and Meijer, 2001). Originally, DGPP was discovered as an in vitro product of PA kinase when ATP was added to plant microsomes (Wissing and Behrbohm, 1993) and later as an in vivo product when cells were stimulated with the G-protein activator mastoparan (Munnik et al, 1996).…”
Section: Discussionsupporting
confidence: 53%
“…After completion of the run, TLC plates were allowed to dry at room temperature and radioactivity was detected by autoradiography (KODAK T-MAX 100). 22 Initial experiments indicated that no differences existed between the phospholipid patterns of the Cf-4/Avr4 and control seedlings when subjected to the temperature shift from 33°C to 20°C, as in both types of seedlings the PA levels increased (data not shown). This increase could result from either the activation of the PLC/DGK pathway or could be caused by increased phospholipase D (PLD) activity.…”
mentioning
confidence: 91%
“…21 DGPP is a common plant phospholipid which is present at trace amounts under resting conditions and accumulates under general stress conditions, in the presence of elicitors and during pathogen infection processes. 3,4,22,23 Several years of extensive research in mammalian systems has expanded our understanding of the important role of PLCs in different aspects of cellular signaling, including immune responses. [24][25][26] Likewise, we recently discovered that also in plants effective innate-immunity requires catalytically active PLC enzymes.…”
mentioning
confidence: 99%
“…Recent work has demonstrated that PI5P levels increase after salt stress (Meijer et al, 2001b). Hyperosmotic stress activates phospholipase D (PLD) activity and induces increased levels of phosphatidic acid (PA; Frank et al, 2000;Munnik et al, 2000;Katagiri et al, 2001;Munnik, 2001;Meijer et al, 2002). In addition, PLD activity is rapidly activated by abscisic acid, a phytohormone involved in the plant cell's response to desiccation Gilroy, 1998, 2000;Jacob et al, 1999;Sang et al, 2001;Hallouin et al, 2002).…”
mentioning
confidence: 99%